LOW COST SOLAR ENERGY EFFICIENCY FOR DESALINATION SYSTEM USING SIMULATION MATLAB - Habib ALzaroug Abobaker Wardeko; Muhammad Haddin; Arief Marwanto; Muhammad Qomaruddin (Journal of Telematics and Informatics, 2018)
Freshwater and energy scarce are now becoming most important issues worldwide. Freshwater or potable water is the most important for human life. The rapid growth of population and industrialization contribute on the freshwater scarce. Conventional energy such as fossil fuel faces the similar trend with freshwater scarce since it is not renewable. The price of conventional energy is increased along with the scarcity. Desalination techniques have been developed for decades to be alterative way in providing freshwater. The desalination processes are driven by energy either thermal, mechanical and electricity.Efficiency for desalination system using simulation/Matlab, driven by renewable energy has derived great attention from scholars and engineer worldwide to get over freshwater need and energy issues. One of major concern in this field is to develop low cost desalination system that driven by renewable energy.